Responsivity and relation to depressive symptoms of occupational behavior and experience patterns - Lilia Papst; Christian Zickwolf; Michael Käfer; Volker Beierlein; Volker Köllner; Volker Köllner (Frontiers Media S.A., 2023)
IntroductionWork stress is a frequent factor in the development of depression. However, not only workplace environment, but also personal attitudes may affect stress experience. The aim of this study was to investigate the change sensitivity of occupational attitudes in psychosomatic inpatients and assess the relationship of changes to depressive symptom reduction.MethodsThe data set encompassed N = 1708 inpatients from two German psychosomatic rehabilitation clinics at admission and discharge. Responsivity of AVEM measures was evaluated by Bonferroni-corrected t-tests and Cohen's dz effect sizes for paired samples. The relation of occupational behavior and experience patterns and depressive symptoms as assessed by the BDI-II questionnaire was calculated by Pearson correlation analysis of pre-post differential values.ResultsChanges in work attitudes were found on eight out of eleven AVEM subscales (Padj ≤ 0.001, Cohen's dz = −0.45 to 0.43) and all AVEM coping styles. Most patients (57.4%) were classified to have a Burnout occupational coping style at admission. Changes following rehabilitation were most frequently observed from Burnout to Sparing coping styles (8.3%). Small to moderate associations between changes in occupational attitudes and depressive symptom reduction were found for all subscales (r = −0.39 to 0.25) except work ambition, and for occupational coping styles Burnout (r = 0.19), Sparing (r = −0.18) and Healthy (r = −0.10), but not Ambitious.DiscussionThe data support responsivity of occupational behavior and experience patterns within a psychosomatic rehabilitation setting. Correlations with depressive symptom reduction suggest that occupational attitudes are related but separate treatment targets.